2015
DOI: 10.1038/srep11402
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and proteomic analysis of pre-diapause and non-diapause eggs of migratory locust, Locusta migratoria L. (Orthoptera: Acridoidea)

Abstract: Low temperature induces diapause in locusts. However, the physiological processes and initiation mechanism of diapause are not well understood. To understand the molecular basis of diapause, ‘omics’ analyses were performed to examine the differences between diapause and non-diapause eggs at both transcriptional and translational levels. Results indicated that a total of 62,241 mRNAs and 212 proteins were differentially expressed. Among them, 116 transcripts had concurrent transcription and translation profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 50 publications
1
58
0
Order By: Relevance
“…In the non‐oxidative phase of the PPP, TKT2 links the PPP and the glycolysis pathway, which suggests that the increase of TKT2 in DD females may induce lipid storage. In the migratory locust, Locusta migratoria , several transketolases were upregulated in prediapause eggs (Tu et al ., ). Hence TKT upregulation may be a common feature of the DPP in different insects and diapause types.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In the non‐oxidative phase of the PPP, TKT2 links the PPP and the glycolysis pathway, which suggests that the increase of TKT2 in DD females may induce lipid storage. In the migratory locust, Locusta migratoria , several transketolases were upregulated in prediapause eggs (Tu et al ., ). Hence TKT upregulation may be a common feature of the DPP in different insects and diapause types.…”
Section: Resultsmentioning
confidence: 97%
“…We found that ALDH1 expression was higher in DD females compared to NDD females (Figs E and S3E), which suggests that ALDH1 is also involved in the fat hypertrophy of DD insects. In studies of other types of insect diapause, such as embryonic diapause in L. migratoria (Tu et al ., ), larval diapause in Nasonia vitripennis (Wolschin & Gadau, ) and pupal diapause in H. armigera (Lu & Xu, ), ALDH mRNA or protein was generally upregulated in DD individuals during the prediapause and early diapause stages. Expression of this gene also increased in DD embryos of the shrimp A. franciscana (Qiu et al ., ), suggesting that its role in regulating animal diapause is highly conserved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no extensive and comprehensive studies have been made on the effects of serpin in relation with insect diapause. Keeping in view the importance of serpins in other plants and animals, this novel study was designed to carry out the transcriptome analysis of diapause and nondiapause eggs of migratory locust, L. migratoria , especially for the serpin genes [21,22]. We further performed label‐free proteomic sequencing on diapause and nondiapause eggs of migratory locust to understand the expression of serpin‐related genes [21,22].…”
mentioning
confidence: 99%